Pengaruh Iklan Heritage Terhadap Brand Awarenes, Brand Trust, Dan Intensi Pembelian - Happy Sandra; Jony Oktavian Haryanto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
This study is aimed to determine how the influence of heritage advertising, brand awareness and brand trust in creating the intention to buy. This study took 130 respondents and using purposive sampling method. Data analysis techniques used confirmatory factor analysis and structural equation modeling with software LISREL 8.80. The results showed that heritage ads significantly influence brand awareness but not for brand trust and intention to buy. On the other hand, brand awareness significantly influences brand trust as well as intention to buy. Furthermore, brand trust significantly influences intention to buy. Thus, a service provider needs to develop heritage advertising as its function to develop brand awareness which finally create intention to buy. A service provider has to maintain and develop brand awareness because it will create brand trust and intention to buy.